(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
During six months visual censuses were carried out in two mangrove lagoons in the island of Tintipán, Colombian Caribbean. Twenty-six species of juvenile reef fishes were observed, some of them with economical importance in the region. The importance of the lagoons as nurseries for fishes is presented and one dynamite illegal fishing event is reported.